Colorectal endoscopic submucosal dissection can be efficiently performed by a trainee with use of a simple traction device and expert supervision - Ide, Daisuke; Saito, Shoichi; Ohya, Tomohiko Richard; Nishikawa, Yuske; Horie, Yoshimasa; Yasue, Chihiro; Chino, Akiko; Igarashi, Masahiro; Saruta, Masayuki; Fujisaki, Junko (Endoscopy International Open, 2019)
Background and study aims Colorectal endoscopic submucosal dissection (ESD) is technically challenging owing to submucosal fibrosis and difficult endoscope manipulation. Therefore, various traction methods have been reported. We often use a simple looped nylon thread attached to a clip to assist with dissection. We assessed the feasibility of mentor-guided colorectal ESD using this traction device (TD). Patients and methods From December 2017 to March 2018, we retrospectively reviewed outcomes of 101 colorectal ESDs performed by two groups of endoscopists (A, 5 endoscopists with colorectal ESD experience of < 50 cases; B, 5 endoscopists with experience of > 300 cases). Group A was further divided into two subgroups that performed ESD with or without TD.Results No significant difference was observed in ESD completion rates (86.1 % [62/72] vs. 96.6 % [28/29]; odds ratio [OR], 0.22; 95 % conﬁdence interval [CI], 0.005 – 1.71; P = 0.17) or procedure times (52.0 min vs. 40.0 min; P = 0.27) and adverse event rates between groups A and B. The rate of TD use was significantly higher in group A than in group B (44.4 % [32/72] vs. 20.7 % [6/29]; OR, 3.03; CI, 1.04 – 10.23; P = 0.03). The completion rate was not different between the two subgroups of group A (with vs. without TD) (81.2 % [26/32] vs. 90.0 % [36/40]; OR, 0.49; CI, 0.09 – 2.29; P = 0.32); however, the proportion of fibrosis cases was significantly higher in the TD-use group (46.8 % [15/32] vs. 22.5 % [9/40]; OR, 2.99; CI, 0.98 – 9.59; P = 0.03). Conclusion Mentor-guided colorectal ESD using TD was performed efficiently, safely, and in a manner comparable to that of experts.